Pengaruh Influencer Marketing dan Live Streaming terhadap Perilaku Pembelian Skintific di Tiktok Shop dengan Niat Pembelian sebagai Variabel Mediasi - Irrawati, Mei Dian; Isa, Muzakar (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research aims to analyze the influence of influencer marketing and live streaming on purchase intentions and purchasing behavior for skintific products on the TikTok Shop platform. Research methodology: A quantitative approach was used by collecting data through a survey of 200 respondents who have interacted with Skintific products via TikTok Shop. Partial Least Squares (PLS) analysis was employed to examine the relationships between variables. Results: The results indicate that influencer marketing has a positive and significant impact on purchase intention, with factors such as expertise, attractiveness, and credibility of influencers playing a key role. Additionally, the live streaming feature shows a significant influence on purchase intention, creating an interactive shopping experience that enhances consumer trust. Purchase intention is proven to mediate the relationship between influencer marketing and purchasing behavior, as well as between live streaming and purchasing behavior. Conclusions: Influencer marketing and live streaming on TikTok Shop have a significant impact on consumers' purchase intentions and behaviors. Influencers who possess expertise, attractiveness, and credibility are able to build positive perceptions that enhance consumers' intention to buy a product. Additionally, the interactive features of live streaming such as live product reviews and Q&A sessions create a convincing shopping experience, making consumers feel more confident and interested in the featured products. Purchase intention not only serves as the initial step in the decision-making process but also reinforces the influence of influencer marketing and live streaming on consumer purchasing behavior. Limitations: : Limited to TikTok Shop consumers and focused on Skintific products, so the results may be less generalizable to other e-commerce platforms or products. Contribution: field of digital marketing, academic.